Catalytic pyrolysis of biomass wastes over Org-CaO/Nano-ZSM-5 to produce aromatics: Influence of catalyst properties. (December 2019) - Yi, Linlin; Liu, Huan; Li, Sihan; Li, Meiyong; Wang, Geyi; Man, Gaozhi; Yao, Hong
Graphical abstract: Highlights: The BTX production by Org-CaO/NZSM-5 is almost twice as that by conventional CaO/ZSM-5. The proportion of aromatics and BTX with Org-CaO/NZSM-5 were up to 93% and 54%. Org-CaO contributed to BTX formation during dual catalytic pyrolysis. NZSM-5 promoted the conversion of bulky molecules into naphthalenes. Abstract: Catalytic pyrolysis of biomass wastes is a promising way to produce aromatics. Based on the conventional CaO/ZSM-5 system, this study aims to improve the aromatics yields by developing an upgraded system which combined nanosized ZSM-5 with CaO from organic calcium precursors (Org-CaO/NZSM-5). The results showed that the aromatics proportion in bio-oil from pyrolysis of Jatropha de-oiled cake with Org-CaO/NZSM-5 increased to 93%. The corresponding yield of BTX (benzene, toluene and xylene) and naphthalene was around 70% which was almost twice than that with conventional CaO/ZSM-5. Org-CaO showed better thermal cracking ability and deoxygenation with more hydrocarbons intermediates and higher H/Ceff of vapors, contributing to enhanced formation of BTX over NZSM-5. NZSM-5 contained much more mesopores and acid sites on external surface, promoting higher conversion of bulky molecules into naphthalenes. Compared with peanut shell, corncob and bagasse pyrolysis, Jatropha de-oiled cake pyrolysis produced much higher aromatics with Org-CaO/NZSM-5.